2018
DOI: 10.1002/pola.29064
|View full text |Cite
|
Sign up to set email alerts
|

Introducing flexibility in urea–formaldehyde resins: Copolymerization with polyetheramines

Abstract: Adhesives obtained by copolymerizing urea, formaldehyde, and difunctional polyetheramine with different molecular weights (230, 600, 900, and 2000 g mol−1) are presented as a more resilient alternative to conventional urea–formaldehyde resins. Urea and polyetheramine contents were varied and the resulting resins characterized by FTIR, 13C‐NMR, and TGA. These resins were used for production of agglomerated cork panels, an application that demands that the binder system is flexible. Polyetheramine with molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…1,3,5-Trihydroxybenzene and 2-nonylphenol were introduced into the UF resin synthesis system to prepare phloroglucinolnonylphenol-urea-formaldehyde (P-NP-UF) co-condensed resin. The results of FTIR and 13 C NMR analysis showed that benzene ring and long-chain alkyl structure were successfully introduced into the molecular structure. Compared with UF resin, the peak curing temperature (T p ) of cocondensed resin moved to a lower temperature and the apparent activation energy decreased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,3,5-Trihydroxybenzene and 2-nonylphenol were introduced into the UF resin synthesis system to prepare phloroglucinolnonylphenol-urea-formaldehyde (P-NP-UF) co-condensed resin. The results of FTIR and 13 C NMR analysis showed that benzene ring and long-chain alkyl structure were successfully introduced into the molecular structure. Compared with UF resin, the peak curing temperature (T p ) of cocondensed resin moved to a lower temperature and the apparent activation energy decreased.…”
Section: Discussionmentioning
confidence: 99%
“…The spectral resolution was 4 cm −1 , and the scanning rate was 20 min −1 . Solid-state 13 C NMR analysis of P-NP-UF resin was performed on a Bruker Avance III spectrometer (Switzerland). The curing kinetics of the resin was measured by using Netzsch 204 differential scanning calorimeters (Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…How to balance the formaldehyde emission and performance? In recent years, modifications of UF and MUF resins with linear 26,27 and hyperbranched polymers have been reported. Especially modifications with poly(amidoamine)s with different end groups such as −NH 2 (aliphatic), −OH (aliphatic), −CHO, and −COO− were intensively studied in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…How to balance the formaldehyde emission and performance? In recent years, modifications of UF and MUF resins with linear , and hyperbranched polymers have been reported. Especially modifications with poly­(amidoamine)­s with different end groups such as −NH 2 (aliphatic), −OH (aliphatic), −CHO, and −COO– were intensively studied in the literature. Highly branched structure and high functionality of the involved polymers resulted in improved bonding performance, durability, storage stability, and reduced formaldehyde emission level.…”
Section: Introductionmentioning
confidence: 99%